A Pilot Epidemiological Exploration of Regenerative Dentistry From the Perspective of Active Clinicians Working in the UK - Neves, Vitor C. M.; Jamal, Hasan (Frontiers in Dental Medicine, 2021)
Innovation has always been part of dentistry and with that comes thinking outside the box to produce guidelines for implementation of new approaches. Regenerative Dentistry (RD) is a young speciality within the profession, which gathers knowledge from stem cells, molecular biology, and tissue and material engineering to produce and apply novel biologically based therapies. Since RD is an emerging branch of dentistry, it is not yet understood whether active clinicians are aware of this field and know exactly what it does. The aim of this study is to explore the awareness, understanding and beliefs about regenerative dentistry of active dentists. A random selection of active dentists in the UK were approached via email and face to face and asked to fill in a questionnaire. A total of 45 responses were received and analysed. The results showed that active dentists in the UK are aware of the field but are not prepared to apply personalised biologically based therapies and feel a desire to educate themselves about regenerative dentistry further. Also, the results shine a light on the opportunities for regulatory and educational bodies to work together to prepare the clinicians for this novel field. Our research suggests that active dentists are ill-prepared for an era of personalised biologic-based dental treatments. Further thinking of how to implement basic and more advanced biological knowledge and their application in dentistry is needed, and suggestions are made here.